Enhancing Brand Recognition through Simplified Visual Identity: Impact and Benefits - Cui Can (SHS Web of Conferences)
This study on the simplification of brand visual identity primarily explores the necessity of simplifying brand logos and visual elements and their impact on brand recognition. The findings indicate that a simplified visual identity not only enhances brand recognition in digital environments but also improves consumer memory and associations with the brand. By reducing extraneous design elements, brand imagery can more intuitively convey core values while maintaining consistency across multiple platforms. Additionally, minimalist design aligns with modern consumers’ aesthetic preferences, projecting professionalism and a sense of trendiness, thereby enhancing the brand’s market competitiveness. Simplified design also facilitates cross-cultural communication for brands in the global market, increasing their international influence. This paper summarizes the various advantages of simple visual design and offers several practical recommendations, providing theoretical support for brands seeking sustainable development in a complex and dynamic market environment. The study employs literature review and case analysis methods. Using the well-known automotive brand Audi as a case study, it analyzes the need to balance visual simplicity with brand uniqueness during the simplification process to avoid the loss of brand personality.